0609 Sleep Phenotypes in Middle-Aged and Older Hispanics/Latinos. Results from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). (27th May 2020) - Wu, B; Tarraf, W; Wallace, D M; Stickel, A; Schneiderman, N; Redline, S; Patel, S R; Gallo, L C; Mossavar-Rahmani, Y; Daviglus, M; Zee, P C; Talavera, G A; et al.
Abstract: Introduction: Identifying sleep phenotypes in the diverse and understudied US Hispanic/Latino population is critical to developing interventions and mitigating distal clinical outcomes (e.g. dementias). Methods: Using latent class analyses (LCA), we identify empirically derived and clinically meaningful sleep phenotypes using data on community dwelling middle-aged/older adults (ages ≥45-years) from the HCHS/SOL (2008-2011) - Investigation of Neurocognitive Aging (n=6, 377). Sleep variables used included Apnea/Hypopnea Index (AHI), percent time SpO2<90%, Epworth Sleepiness Scale (ESS), Women's Health Initiative Insomnia Rating Scale (WHIIRS), self-reported average sleep duration, restless legs symptoms, napping frequency, and sleep quality. Results: Mean (M) age was 56.4±8.1 years, and 54.7% were female. Average AHI, ESS, WHIIRS, and sleep duration were 8.7±13.1, 6.0±5.0, 7.6±5.5, and 7.8±1.4, respectively, and 25.8% had zero percent time SpO2 <90%. Fit statistics indicated that a four-class solution provided the best data fit. The derived classes, adjusting for age, sex, income, and acculturation, corresponded with four clinically meaningful groups: (1) 28.8% were asymptomatic [(M) AHI=0.8; (M) ESS=5.6; (M)WHIIRS=7.6; (M) sleep duration=7.8; 0% SpO2<90%=74.1% ], (2) 25.7 % were asymptomatic mild sleep apnea [(M) AHI=6.2; (M) ESS=3.8; (M) WHIIRS=2.9; (M) sleep duration=7.8; 0% SpO2<90%=8.8% ], (3) 19.4% were symptomatic sleep apnea [(M) AHI=25.6; (M) ESS=8.5; (M) WHIIRS=7.2; (M) sleep duration=7.7; 0% SpO2<90%= 0.5% ], and (4) 26.1% were insomnia [(M) AHI=5.7; (M) ESS=6.7; (M) WHIIRS=13.0; (M) sleep duration=7.8; 0% SpO2<90%=10.3% ]. Classification into groups 3 and 4 were primarily driven by elevated AHI and WHIIRS scores, respectively. The distribution of scores in the derived groups suggest variations relative to current clinical thresholds. Conclusion: We identified 4-groups using LCA in a community-based sample of diverse U.S. Hispanic/Latino adults. Better characterization of sleep phenotypes for Hispanics/Latinos can help in developing targeted interventions studies and ameliorate health disparities. Support: 5R01AG048642-05; R21AG056952; R21HL140437.